+0  
 
0
53
2
avatar+278 

Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

 

 

Thanks my dudes!

AnonymousConfusedGuy  Nov 28, 2017
Sort: 

2+0 Answers

 #1
avatar+5589 
+3

Hmm...well......I could be wrong here, but here's what I was thinking:

 

Since  f(0)  =  47 , we know that the constant term is  47 .

 

Since  f(1)  =  32 , we know that  the sum of the coefficients + 47  =  32

 

the sum of the coefficients + 47  =  32   so

the sum of the coefficients  =  -15

hectictar  Nov 28, 2017
 #2
avatar+1493 
+2

Your logic is spot on!

TheXSquaredFactor  Nov 28, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details